Staphylococcus lugdunensis Septic Arthritis following Arthroscopic Anterior Cruciate Ligament Reconstruction - Saygin Kamaci; Yehia H. Bedeir; Christopher J. Utz; Angelo J. Colosimo (Case Reports in Orthopedics)
Summary. We report two cases of Staphylococcus lugdunensis (S. lugdunensis) septic arthritis following arthroscopic anterior cruciate ligament (ACL) reconstruction. Both initial surgical procedures were ACL reconstruction along with simultaneous collateral ligament and meniscus procedures. Patients presented with septic arthritis three and ten weeks following the index procedure. Both patients successfully recovered with early arthroscopic irrigation, debridement, and synovial culture, in addition to long-term parenteral and oral antibiotics.